Language Learning in Modular Set-Up: Challenges and Coping Mechanisms of Secondary Students - Wilmarie S. Francisco; Ericson O. Alieto (Future Science, 2022)
The urgent need to respond to the Covid crisis has provided the impetus for the implementation of modular distance learning in the Philippines. Hence, this study is one of the very few studies which sought to investigate the modular distance learning in the country, particularly the challenges it brought to the English language learners. Also, this present research aimed to determine the coping mechanisms of students, relevant to the challenges raised. The participants of the study were senior high school students, two males andsixfemales, who were purposely selected to fit into the inclusion criteria. Descriptive qualitative research design was employed and individual in-depth interviews were conducted to gather the data. The responses were transcribed, translated, and analyzed through thematic analysis. With regards the challenges, these themes were created: absence of teacher’s instruction, struggles of self-learning, poor picture quality, limited contents of the module, insufficient allotted time, failure of teachers to respond to inquiries, unstable and limited access to internet, students lack of vocabulary and grammatical knowledge, and less opportunity for correction. The paper ends with the discussion on how the students addressed the challenges of modular distance learning which was also subdivided into themes.